Kemampuan Berpikir Kreatif Peserta Didik Melalui Model ReCODE Pada Pembelajaran Biologi - Suhartini Azis (Departement of Mathematics Education, 2024)
This research is based on the skills that students must possess in line with the development of 21st-century education, one of which is creative thinking. The aim of this study is to describe students' creative thinking skills using the Reading Connecting Observing Discussing Evaluating (ReCODE) model in biology learning at SMA Negeri 3 Bantaeng, South Sulawesi Province. The research design used is a quasi-experiment with the static group pretest-posttest design. The population in this study is all Class XI, and the sample used is Class XI IPA1 as the control group using the conventional model (lecture and question-answer) and Class XI IPA2 as the experimental group using the ReCODE model. Students' creative thinking skills are measured using a test that includes four indicators: fluency, originality, elaboration, and metaphorical thinking. The data analysis technique used is the analysis of covariance (ancova) using SPSS Windows version 26. The research results show that the mean score of creative thinking skills using the ReCODE model (experimental class) is higher at 86.94 compared to the conventional model (control class) at 79.34. From the ancova analysis, a significant value of 0.004 was obtained, which is smaller than the alpha value of 0.05, indicating that creative thinking skills are influenced by the ReCODE learning model. Additionally, the ReCODE learning model is 17.6% better compared to the conventional learning model. Therefore, it can be concluded that the use of the ReCODE learning model influences and can improve the creative thinking skills of Class XI students at SMA Negeri 3 Bantaeng.